Банда 2: роман / Виктор Пронин - Пронин Виктор Алексеевич (Надежда- 1, 1996)
Экземпляры: ф.16 (2004) / Инвентарный номер: 48065 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 81 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445.7